Growth of well-arrayed ZnO nanorods on single-mode silica fiber and evaluation of its light scattering - Idris, N.F.; Lukman, Muhammad Quisar; Abdul Rahim, Hazli Rafis; Saidin, Norazlina; Yasin, M.; Harun, Sulaiman Wadi (John Wiley and Sons Inc., 2017)
Light scattering by zinc oxide (ZnO) nanorods at different growth duration is investigated. Synthesis of ZnO nanorods was done using hydrothermal techniques on the surface of bare silica optical fiber at different growth duration ranging from 4 to 10 hours. Both physical and optical characterizations were accomplished to investigate the morphology of ZnO and light scattering effect, respectively. The samples with different growth times were analyzed using the field emission scanning electron microscopy (FESEM) image to estimate the length, diameter and density of nanorods grown on the curve surface of bare fiber. At growth duration of 10 hours, the length, diameter, and density of nanorods are 928.85 nm, 185.77 nm, and 43.33 3 1012 nanorods/m2, respectively. Optical characterization was performed by measuring the output spectrum of the transmission light, the result indicates that the scattering effect increases with the growth durations.